PENDAPATAN DAN KESEJAHTERAAN RUMAH TANGGA PETANI PADI PENGOLAH IKAN ASAP DAN NON PENGOLAH IKAN ASAP (KASUS DI DESA KEBON DAMAR, KECAMATAN MATARAM BARU, KABUPATEN LAMPUNG TIMUR) - Susanto, Susanto; indriani, yaktiworo; Riantini, Maya (Lampung University, 2021)
This research aims to calculate the income and welfare of rice farmers who processsmoked fish and who do not process. The research was carried out in Kebon Damar Village from July to August 2019 using a survey method. The determination of the sample was done in stage (multistage sampling). The sample in this research amounted to 57 rice farmers. The data were analyzed using income analysis, R-C ratio, and household welfare according to the 1997 Sajogyo’s criteria. The results showed that the largest contribution of household income of nonsmoked fish processing ricefarmers came from rice farming or 71.45 percent of the total household income. Whereas, the largest contribution of household income of smoked fish processing rice farmers came from the smoked fish processing business or 54.43 percent of the total household income. Smoked fish processing rice farmers weremore prosperous than nonsmoked fish processing rice farmers.Keywords: Household income, household welfare, rice farmers, smoked fish.